Individual differences in subjective circadian flexibility. (21st October 2015) - Marcoen, Nele; Vandekerckhove, Marie; Neu, Daniel; Pattyn, Nathalie; Mairesse, Olivier
Abstract : The aim of this study was to evaluate individual differences in the subjective flexibility of the circadian system in a community sample, with respect to age, gender, chronotype, and sleepiness perceptions. An online questionnaire containing the Circadian Type Inventory, the Composite Scale of Morningness, the Pittsburgh Sleep Quality Index and the Epworth Sleepiness Scale was administered. In addition, participants performed a visuo-verbal judgment task to determine time-of-day variations in estimated sleepiness. We analyzed data of 752 participants, aged between 18 and 83 years, who reported good sleep quality, no sleep disturbances, no excessive daytime sleepiness, and no engagement in shiftwork. Our results suggest gender- and chronotype-related differences in the subjective flexibility of the circadian system. Subjective circadian flexibility was higher in men in comparison with women and was positively related to evening preference. Age was not associated with flexibility scores. Additionally, the subjective flexibility of the circadian system had an influence on estimated sleepiness profiles: individuals with a high flexibility displayed lower sleepiness estimations during the biological night in comparison to individuals with a low flexibility. These findings suggests that, next to known chronotype and other dispositional differences, subjective circadian flexibility should be taken into account when evaluating tolerance to activities associated with nighttime functioning (e.g. night shifts).